Efficacy of hypnotherapy compared to cognitive-behavioural therapy for mild-to-moderate depression: study protocol of a randomised-controlled rater-blind trial (WIKI-D). Issue 11 (1st December 2017) - Fuhr, Kristina; Schweizer, Cornelie; Meisner, Christoph; Batra, Anil
Abstract : Introduction: Despite a substantial number of studies providing evidence for the efficacy of psychological treatment for mild-to-moderate depression, maximally only 50% of participants respond to treatment, even when using gold-standard treatments such as cognitive-behavioural therapy (CBT) and interpersonal therapy. New approaches such as the 'third wave' psychotherapies have provided promising results; however, studies concerning the comparison with evidence-based treatments are lacking. This study aims to compare the efficacy of clinical hypnotherapy (HT) with gold-standard psychotherapy (CBT) in the treatment of mild-to-moderate major depressive episodes. Methods and analysis: The present study comprises a monocentric, two-armed, randomised-controlled, rater-blind (non-inferiority) clinical trial. A total of 160 participants with mild-to-moderate major depression episode will be randomly assigned to either CBT or HT involving 20 sessions of psychotherapy over a period of 24 weeks. We predict that the average improvement in the Montgomery-Åsberg Depression Rating Scale score will not be inferior in HT compared with CBT (non-inferiority hypothesis). Further outcome parameters will include the number of participants responding to treatment following the completion of treatment and 1 year after. Additionally, quality of life, treatment expectations and hypnotic susceptibility before and after end of treatment will be assessed. Ethics and dissemination: The study protocol and the documents for the informed consent have been approved by the Ethics Committee of the University Hospital Tuebingen (061/2015B02). The results of this trial will be submitted for publication in peer-reviewed journals, and will be presented at national and international conferences. Trial registration number: NCT02375308; Pre-results.